Analisis persepsi pengunjung terhadap fungsi Taman Kumbasari Tukad Badung, Denpasar Barat sebagai ruang terbuka non-hijau - Alodia, Made Olga; Semarajaya, Cokorda Gede Alit; Sukewijaya, I Made (Jurnal Arsitektur Lansekap, 2020)
Analysis of visitor perception to the function of Kumbasari Park, Tukad Badung, West Denpasar asnon-green open space. Kumbasari Park is the result of the arrangement of Tukad Badung into a public nongreen open space that is used as a recreation place in the crowd of Denpasar City. This research aimed to determine and analyze visitors' perceptions of the function of Kumbasari Park as a non-green open space, as well as giving an input for the maintainer to improve the quality of Kumbasari Park in the future. The researchmethod was surveyed through site observation, interviews, and questionnaires. The results of this research indicated that Kumbasari Park mainly functioned as the visual beauty of the city, and also functioned as a non-green open space seen from the socio-cultural, ecological, economic, and architectural functions category.Some things related to Kumbasari Park that need attention was the issues of cleanliness, vandalism, aroma,vegetation, and facilities. Suggestions related to this research were facilities and management in KumbasariPark needed to be improved to be able to attract visitors.